Vaccine safety in the next decade: why we need new modes of trust building - Larson, Heidi J. (BMJ Glob Health, 2021)
Among the realm of highly varied vaccine perceptions and concerns expressed by publics around the world, vaccine safety is the most frequently cited. While many of the safety questions raised have substantial evidence to address the concerns, vaccines do have small risks, and need vigilant and responsive systems to address them. With more and more new vaccines, combinations of vaccines and new technologies to develop and deliver them, new safety concerns will arise that need attention. Adding to this landscape is the dramatic impact which digital communication has had on how fast rumours and vaccine concerns can spread, making the task of the public health and scientific community even more pressing. One of the more recently characterised vaccine safety issues, now named ‘immunisation stress-related-response,’ has gained particularly high visibility given these highly globally connected social media networks. To better anticipate and address these rapidly shared vaccine safety concerns, a number of global efforts and local responses are being made. Co-created social media campaigns engaging parents and adolescents have been effective, while the WHO’s Vaccine Safety Net (VSN) initiative has grown its global network to increase awareness about vaccines and contribute to building confidence in vaccines. The VSN reviews websites around the world to assess their quality and accuracy to ensure and promote access to trustworthy and science-based information on vaccine safety for internet users. These and the efforts of the multiple network partners are more crucial than ever to sustain public confidence in this evolving vaccine safety landscape.